Autophagy and Cancer: Insights into Molecular Mechanisms and Therapeutic Approaches for Chronic Myeloid Leukemia - Mohd Adnan Kausar; Sadaf Anwar; Yusuf Saleem Khan; Ayman A. Saleh; Mai Ali Abdelfattah Ahmed; Simran Kaur; Naveed Iqbal; Waseem Ahmad Siddiqui; Mohammad Zeeshan Najm (Biomolecules, 2025)
Autophagy is a critical cellular process that maintains homeostasis by recycling damaged or aberrant components. This process is orchestrated by a network of proteins that form autophagosomes, which engulf and degrade intracellular material. In cancer, autophagy plays a dual role: it suppresses tumor initiation in the early stages but supports tumor growth and survival in advanced stages. Chronic myeloid leukemia (CML), a hematological malignancy, is characterized by the Philadelphia chromosome, a chromosomal abnormality resulting from a translocation between chromosomes 9 and 22. Autophagy has emerged as a key factor in CML pathogenesis, promoting cancer cell survival and contributing to resistance against tyrosine kinase inhibitors (TKIs), the primary treatment for CML. Targeting autophagic pathways is being actively explored as a therapeutic approach to overcome drug resistance and enhance cancer cell death. Recent research highlights the intricate interplay between autophagy and CML progression, underscoring its role in disease biology and treatment outcomes. This review aims to provide a comprehensive analysis of the molecular and cellular mechanisms underlying CML, with a focus on the therapeutic potential of targeting autophagy.